Potencial zoonótico da Criptosporidiose canina: revisão sistemática - Ribeiro, Rafaela Silva de Paula [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Until recently, human cryptosporidiosis was attributed only to human and bovine genotypes. However, other species such as Cryptosporidium canis, are able of causing infection in humans. Due to this, criptosporidiosis has caused a great interest in the public health field. The objective of this study was to investigate the real zoonotic potential of canine cryptosporidiosis, analyzing whether dogs should be considered an important source in the transmission of this disease to humans. Ten articles from PubMed, Science Direct and Scopus databases were selected for this systematic review. The main search strategy was Cryptosporidium AND dogs AND epidemiology, selecting only articles in written in english and with a maximum of five years of publication. The studies were classified according to the degree of recommendation (PHILLIPS et al., 2001). According to the literature, the main specie isolated in dogs was C. canis, which is a species-specific canine agent, but other species, such as Cryptosporidium hominis, were also isolated to a lesser extent. This specie is also known for being able to infect humans. However, due to the equal division of authors who agree or disagree about the importance of dogs regarding the zoonotic transmission of Cryptosporidium, it can be considered that the role of this host in relation to human cryptosporidiosis has not yet been defined

A criptosporidiose humana, até recentemente, era atribuída apenas aos espécies humanos e bovinos porém, atualmente, considera-se que outras espécies, como o Cryptosporidium canis, possam ser causadores da infecção no homem. Devido a isto esta enfermidade tem gerado grande interesse na área de saúde pública. O objetivo deste estudo foi averiguar qual o real potencial zoonótico da criptosporidiose canina, analisando se, de fato, o cão deve ser considerado uma fonte de infecção importante na transmissão desta enfermidade para os humanos. Para esta revisão sistemática foram utilizados dez artigos científicos, provenientes dos bancos de dados PubMed, Science Direct e Scopus. A principal estratégia de busca utilizada foi Cryptosporidium AND dogs AND epidemiology, empregando-se como filtro artigos na língua inglesa e com no máximo cinco anos de publicação. Os trabalhos foram classificando de acordo com o grau de recomendação (PHILLIPS et al., 2001). Segundo a literatura utilizada, a principal espécie isolada nos cães foi C. canis, que é espécie-específica dos caninos, porém também foram detectadas, em menores proporções, outras espécies, dentre elas Cryptosporidium hominis, a qual é bem conhecida por infectar pessoas. Entretanto, devido à divisão igualitária de autores a favor e contra a importância dos cães quanto a transmissão zoonótica do Cryptosporidium, pode-se considerar que o papel deste hospedeiro em relação à criptosporidiose humana ainda não está definido
Keywords: Cães; Epidemiologia; Cryptosporidium; Saúde pública; Public Health